Archaeozoology of the Near East XII. Proceedings of the 12th International Symposium of the ICAZ Archaeozoology of Southwest Asia and Adjacent Areas Working Group, Groningen Institute of Archaeology, June 14-15 2015, University of Groningen, the Netherlands - Çakirlar, Canan; Chahoud, Jwana; Berthon, Remi; Pilaar Birch, Suzanne E. (Barkhuis Publishing & University of Groningen, 2018)
The first international meeting of the Archaeozoology of Southwest Asia and Adjacent Areas (ASWA) working group of the International Council for Archaeozoology (ICAZ) took place at the University of Groningen in 1992. Ever since, ASWA meetings have served as an inspiring gathering for those conducting archaeozoological research in Southwest Asia, the Eastern Mediterranean, North Africa, Central Asia and the Caucasus. This book contains sixteen papers presented at the 12th ASWA meeting hosted at its inaugural institution, the University of Groningen, Groningen Institute of Archaeology, as a continuation of the usual series and to celebrate the career of Dr. Hijlke Buitenhuis, associated member and alumnus of the institute, co-organizer of the first ASWA meeting.00Like other ASWA proceedings before it, this volume is full of novel theoretical and methodological approaches and new research results, tackling a large variety of topics, from the geometric morphometrics of sheep in the Pre-Pottery Neolithic Period to Predynastic fishing in the Upper Nile, to the biogeography of hartebeest and hemione, and covering the vast region stretching between Hungary in the west and Azerbaijan in the east. The volume also features an opening article by ASWA founding member M.A. Zeder on the future of archaeozoology in the region. In honor of Dr. Hijlke Buitenhuis, his full bibliography is featured herein.